Inflammation Severity in Radicular Cysts and Its Relationship with Age and Gender - Çelik, Mürüvvet Akçay; Erdem, Havva; Salman, Fadime Gül; Erdem, Busra; Balta, Hılal; Arıcı, Yeliz Kasko; Korkmaz, Özge Kaya (My University, 2024)
Aim: In this study, in radicular cyst cases in our department; It was aimed to evaluate the severity of inflammation (active and chronic inflammation) and to investigate its relationship with age and gender. Material and Method: Radicular cyst cases between 01.01.2013 and 31.01.2022 in Ordu University, Faculty of Medicine, Department of Pathology were included in the study. Ethical approval was taken from Ordu University Medical School, Clinical Trials Ethical Committee (2022/82). Preparations of the cases were found from the archive and examined microscopically to score the severity of inflammation. To examine any relationships that existed between categorical variables, Chi-square test was used. To determine any relationships between the score variables, correlation analysis was done. Results: A statistically significant moderate negative correlation was observed between age and chronicity in women (r=-0.410, p=0.013). A statistically significant moderate positive correlation was observed between activity and chronicity scores in men (r=0.592, p<0.001). When all patients were considered, weakly significant negative correlation was found between activity and chronicity (r=0.312, p<0.001). While one was increasing, the other was increasing. Conclusion: In radicular cyst cases, the severity of inflammation may differ from case to case. In our study, the severity of chronic inflammation was observed as high-grade (grade 3) in most of the cases, acute inflammation was found to be mild (grade 1) in most of the cases. It is thought that determining the severity and type of inflammation in the histopathological evaluation may be beneficial for diagnosis and treatment.
Keywords: Inflammation; Radicular Cyst; Odontogenic Cyst